G-Protein-Coupled Estrogen Receptor-1 Positively Regulates the Growth Plate Chondrocyte Proliferation in Female Pubertal Mice - Chou, Ya-Shuan; Chuang, Shu-Chun; Chen, Chung-Hwan; Ho, Mei-Ling; Chang, Je-Ken (Frontiers in Cell and Developmental Biology, 2021)
Estrogen enhances long bone longitudinal growth during early puberty. Growth plate chondrocytes are the main cells contributing to long bone elongation. The role of G-protein coupled estrogen receptor-1 (GPER-1) in regulating growth plate chondrocyte function remains unclear. In the present study, we generated the chondrocyte-specific GPER-1 knockout (CKO) mice to investigate the effect of GPER-1 in growth plate chondrocytes. In control mice, GPER-1 was highly expressed in the growth plate of 4- and 8-week-old mice, with a gradual decline through 12- to 16-weeks. In the CKO mice, the GPER-1 expression in growth plate chondrocytes was significantly less than that in the control mice (an 80% decrease). The CKO mice also showed a decrease in the body length (crown-rump length), body weight, and bone length of tibias and femurs at 8 weeks. More importantly, the cell number and thickness of the proliferative zone of the growth plate, as well as the thickness of primary spongiosa and length of metaphysis plus diaphysis in tibias of CKO mice were significantly decreased compared to those of the control mice. Furthermore, the number of PCNA or Ki67-stained proliferative chondrocytes in the tibia growth plate also showed a significant reduction in the CKO mice. The chondrocyte proliferation function mediated by GPER-1 was further demonstrated by treatment of GPER-1 antagonist in cultured epiphyseal cartilage. The study demonstrates that GPER-1 positively regulates chondrocyte proliferation at the growth plate during early puberty and contributes to the longitudinal growth of long bones.